Data of satellite observation for environmental assessment before and during COVID‐19 pandemic in part of Indonesia using the cloud‐computing platform. (11th March 2022) - Ramdani, Fatwa; Setiani, Putri
Abstract: The global pandemic of COVID‐19 has been insisted by many countries in the world to implement social distancing, including Indonesia. This research measured the environmental impact before and during the COVID‐19 pandemic in Indonesia. Variables, such as nitrogen dioxide (NO2 ) of Sentinel‐5P Tropospheric Monitoring Instrument (Tropomi), nighttime light condition of Visible Infrared Imaging Radiometer Suite (VIIRS) Day/Night Band (DNB) and land surface temperature (LST) of Thermal InfraRed Sensor (TIRS) of Landsat‐8 Operational Land Imager (OLI), were monitored using the cloud‐based computing platform of Google Earth Engine (GEE). This study found that all monitored variables decreased during the period of the COVID‐19 pandemic compared to the period before the pandemic. However, the pattern of reduction of NO2 concentration and nighttime light was not observed to be coherent with large‐scale social distancing regulation enforced by the government. This study found that the reduction has begun 2 months earlier than the official regulation enforced by the government. The lower LST shown in both the time‐series map and the graph demonstrated changes before and during the pandemic. The hypothesis was tested using the t‐test method, and the statistical results show the significant difference between two groups of observed variables (e.g. before and during the pandemic) with the lower p ‐values and higher Cohen's d . Results of this study indicate that it should be feasible to monitor the environmental impact of the COVID‐19 pandemic using the combination of NO2 concentration, nighttime light and LST information as a proxy. Abstract : Global pandemic of COVID‐19 has been insisted many countries in the world to implement social distancing, including Indonesia. This research measured the environmental impact before and during COVID‐19 pandemic in Indonesia. Variables, such as nitrogen dioxide (NO2 ) of Sentinel‐5P, nighttime light condition of VIIRS and land surface temperature (LST) of Landsat‐8 OLI, were monitored using Google Earth Engine (GEE). This study found that all monitored variables decreased during the period of COVID‐19 pandemic compared to the period before the pandemic.